Pengembangan Bahan Ajar Fisika Berbasis Scientific Approach - Wulan Muji Lestari; Tri Ariani; Ovilia Putri Utami Gumay (SPEJ (Science and Physic Education Journal), 2018)
The aim of the study was to develop physic teaching book with scientific approach based on light waves material for the eleventh grade students at SMA Negeri 5 Lubuklinggau. It was a research and development study. The subject in the study was all of the eleventh grade students of science class and the subject was the large group of students at XI IPA 2 at SMA Negeri 5 Lubuklinggau consist of 34 students which was collected through simple random sampling. The data collection was executed from interview, questionnaire, and test. By the validation, it was found that the result was in 'good' category with percentage 76,58%. Students response on the teaching book with scientific approach based was 83,35%. Furthermore, by the daily examination results, 82% students got the average scores above 70 out of 10 questions. The score of ttable with degree of freedom n-1 = 34 ─ 1 = 33 and α = 0,05 tobtained = 6,53 and ttable = 1,692 because tobtained ≥ ttable so that Ha was accepted. In conclusion, the teaching book with scientific approach based which was developed has been valid, practical and effective. Keywords: Teaching Book, Scientific Approach, Reseach and Development